The issue of arranging verses and surahs of the Noble Qur’an in the thought of Abed Al- Jabri through his book Introduction to the Quran - Serhan, Abdurrezzak Abdulkarem; Abay, Ahmed (Journal of Islamic Sciences, 2020)
This study aims to present and discuss the position of Dr. Muhammad Abed al- Jabri on the Qur’an arrangement, and the issue of al- Makki and al- Madani, and to present and discuss his position on the orientalists ’arrangement of the suras of the Noble Qur’an according to descent. It is an analytical study, in which it followed the descriptive, analytical and comparative approach, and the study reached many results, the most important of which are: 1- The most correct view in the Qur’an arrangement is that it is my arrest, not the action of the hard-working Companions. 2- The Companions differed in the order in which the Qur’anic verses were revealed, and they had many narrations regarding that. 3- The interest of the Orientalists was so great that some people thought that researching the history of the Qur’an was one of the innovations of the Orientalists in the sciences of the Qur’an, and we have proven in this research the error of that illusion.